Curved graphitic nanosheets with single-atom Zn − N4 defects within closed-pores assisting sodium ion nucleation for high-efficiency sodium storage - Shuocong Duan; Dandan Wang; Chi Chen; Tong Xiao; Run Ren; Linan Wang; Wenjie Zhang; Yunfeng Chao; Jianhua Zhu; Xinwei Cui (Chemical Engineering Journal, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Effect of zero-valent iron and its oxidation products as alternative electron donor on the partial denitrification performance - Zi-Yue Li; Run-Mei Li; Jia-Min Zhou; Yi-Nan Zhang; Zhe Wang; Yao Zou; Ren-Cun Jin; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Preferential Impacts of the Western-Pacific Subtropical High and Australian High on the Indian Ocean Dipole Phases - Zhanglin Li; Hong-Li Ren; Minghong Liu; Run Wang (Advances in Atmospheric Sciences, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Source-dependent composition and reactivity of effluent organic matter regulating disinfection byproduct formation and cytotoxicity - Liang Zeng; Penghui Du; Guoping Chen; Junwen Zhang; Run Zhou; Dong Ren; Junjian Wang (Water Research, 2026)

Insights into the effect of biochar on single-stage partial denitrification/anaerobic ammonium oxidation process: Nitrogen removal performance and mechanism - Run-Mei Li; Zi-Yue Li; Jia-Min Zhou; Yi-Nan Zhang; Zhe Whang; Yao Zou; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2026)

Temperature-responsive regulation of combined drip and micro-sprinkler systems in greenhouses: an EWM-TOPSIS approach for enhancing tomato heat resilience and irrigation efficiency - Chuan Zhang; Run Xue; Haofang Yan; Imran Ali Lakhiar; Jiangtao Ren; Kinde Negessa Disasa; Muhammad Akhlaq; Shuaishuai Deng (Irrigation Science, 2026)

miR-23a modulates chlorantraniliprole susceptibility by targeting SfGSTs3 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Yong-Po Lv; Bai-Zhong Zhang; Meng-Yuan Zhang; Ling-Ling Cui; Ren-Jie Li; Dong-Mei Chen; Yu-Yang Peng; Run-Qiang Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Response of tomato growth and transpiration under adequate elevated CO2 concentrations coupled with irrigation regimes - Muhammad Akhlaq; Henglu Miao; Chuan Zhang; Run Xue; Haofang Yan; Muhammad Usman Hameed; Jun Li; Jiangtao Ren; Junaid Nawaz Chauhdary; Muhammad Mahmood Ur Rehman (Irrigation Science, 2025)

Complete removal of toxic herbicides and structural insight by a heteromolecular aggregate - Shu-Qin Qin; Wei Xu; Run-Yi Chen; Zi-Wei Lai; Gang Chen; Wen-Cai Ye; Ren-Wang Jiang; David A. Middleton (Journal of Hazardous Materials, 2025)

Post-dynamic behaviors of the saturated loess in the Zhongchuan slide triggered by the Jishishan M6.2 earthquake - Haiping Ma; Keliang Ren; Wenguo Ma; Youzhen Yang; Chen Li; Run Cai (Natural Hazards, 2025)

Resilience Assessment of Tomato Crop Chlorophyll Fluorescence Against Water Stress Under Elevated CO 2 and Protective Cultivation - Muhammad Akhlaq; Henglu Miao; Chuan Zhang; Haofang Yan; Xue Run; Junaid Nawaz Chauhdary; Muhammad Mahmood ur Rehman; Jun Li; Jiangtao Ren (Irrigation and Drainage, 2025)
Water scarcity is a crucial issue that reduces plant growth and yield worldwide. Chlorophyll fluorescence parameters, which are associated with plant growth and yield under water stress, are the most sensitive plant parameters. The mitigation of water stress by elevated CO 2 (e[CO 2 ]) by chlorophyll fluorescence for tomato growth is rare. Tomato plants were grown in a controlled environment chambers (CECs) under eight treatments under controlled environmental conditions for two growing seasons: autumn–winter ( AW ) 2021 and spring–summer ( SS ) 2022. The four irrigation regimes included 40%–50% soil water holding capacity (WHC) (I 1 ), 60%–70% WHC (I 2 ), 80%–90% WHC (I 3 ) and 100% WHC (I 4 ). Eight treatments of four irrigation regimes coupled with e[CO 2 ] (700 μmol·mol −1 ) and ambient CO 2 (a[CO 2 ], 500 μmol·mol −1 ) were designed, respectively: I 1 e[CO 2 ], I 2 e[CO 2 ], I 3 e[CO 2 ], I 4 e[CO 2 ], I 1 a[CO 2 ], I 2 a[CO 2 ], I 3 a[CO 2 ] and I 4 a[CO 2 ], where I 4 a[CO 2 ] was considered the control treatment (CK). The chlorophyll fluorescence parameters maximum photochemical efficiency of PSII ( F v /F m ), photochemical efficiency of PSII ( Ф PSII ), electron transport rate ( ETR ) and photochemical quenching ( qP ) significantly decreased, whereas nonphotochemical quenching ( NPQ ) significantly increased under drought stress. Compared with that under CK, the maximum reduction in F v /F m under I 1 a[CO 2 ] was 14% in AW 2021, whereas it was 19% in SS 2022. The Ф PSII was reduced by 13%–3% and 13%–6% under I 1 a[CO 2 ] in AW 2021 and SS 2022, respectively (under the fixed photosynthetically active radiation range of 125–625 μmol·m −2 ·s −1 ) compared with that in the CK. The ETR and qP decreased under I 1 a[CO 2 ] at their maximum level in AW 2021 and SS 2022 with respect to those in the CK. The results showed that e[CO 2 ] mitigated water stress as the F v /F m , Ф PSII , ETR and qP were increased under water stress coupled with e[CO 2 ]. I 1 e[CO 2 ] was the most influential treatment for chlorophyll fluorescence parameters assessed via principal component analysis ( PCA ) in AW 2021 and SS 2022. This study explained the approach to develop crop resilience against water stress by inducing e[CO 2 ], which will play a vital role in sustainable agriculture under drought stress.

Multi-active-site antibacterial modification of dopamine-hyaluronic acid hydrogel with N-halamine for skin tissue engineering - Chenghao Li; Saren Gerile; Nan Du; Liang Zou; Zhiqiang Wang; Yanfang Liu; Jili Hou; Kuntong Song; Yuanhao Xiao; Hui Ren; Jing Kang; Alideertu Dong; et al. (Carbohydrate Polymers, 2025)

Low-temperature catalytic oxidation of toluene using CeO2@MIL-101(Fe): Stability against water and SO2 - David Murindababisha; Abubakar Yusuf; Kien-Woh Kow; Yong Sun; Run Pan; Yong Ren; George Zheng Chen; Jianrong Li; Chengjun Wang; Jun He (Process Safety and Environmental Protection, 2025)

Understanding the impact of promoters on enhancing and inhibiting the sulphur resistance and regeneration of supported Pd catalysts for complete methane oxidation - Abubakar Yusuf; Yong Ren; Yun Liu; Li Shi; Zhiyu Xiao; Run Pan; Zheng Wang; Hainam Do; Jianrong Li; Jun He (Chemical Engineering Journal, 2025)

Boosting structural stability and air stability towards layered oxide cathodes for potassium ion batteries - Hong Chen; Lu-Kang Zhao; Xuejiao Cheng; Xuan-Wen Gao; Zhaomeng Liu; She-Dong Li; Dong-Run Yang; Tian-Zhen Ren; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Integrated network pharmacology, bioinformatics, and experiment analysis to decipher the molecular mechanism of Salidroside on Gastric cancer via targeting NCOA4-mediated ferritinophagy - Yu Fu; Guiqin Huang; Yawen Cai; Menghui Ren; Run Cheng; Yuhui Chai; Yingdi Wang; Yunqi An; Tianhua Yan; Lingpeng Zhu; Xinxin Liu (Chemico-Biological Interactions, 2025)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Roles of tropical-Pacific interannual–interdecadal variability in forming the super long La Niña events - Run Wang; Hong-Li Ren; Minghong Liu (Climate Dynamics, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

Ordered mesoporous Mg-modified silica to confine MoS2 slabs with high sulfidation and dispersion for higher alcohol synthesis via CO hydrogenation - Ziteng Ren; Yihua Cao; Xueli Yin; Yonghao Gan; Run Cai; Qi Wang; Bo Feng; Yindan Wu; Xiaoping Dai (Fuel, 2024)

Distinct North American teleconnection of the strong El Niños as modulated by the ENSO-annual cycle combination mode - Minghong Liu; Hong-Li Ren; Fang Zhou; Run Wang (Climate Dynamics, 2024)

Distributed bending stiffness estimation of bridges using adaptive inverse unit load method - Run-Zhou You; Ting-Hua Yi; Liang Ren; Hong-Nan Li (Engineering Structures, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

The Experimental Study of Dynamic Response of Marine Riser under Coupling Effect of Multiparameter - Run Zheng; Chunguang Wang; Wentao He; Zhenyang Zhang; Keshun Ma; Mengqi Ren (Journal of Marine Science and Engineering, 2023)
In order to investigate the dynamic response of a marine riser under the coupling effect of multiparameter, a model experiment of a marine riser was designed and carried out. The main parameters of the model test were divided into riser design parameters and flow field parameters. The riser parameters included the elastic modulus, boundary conditions, and top tension forces, and the flow field parameters were the velocities and wave parameters (wave height and period). The riser materials were aluminum (Al) and polymethyl methacrylate (PMMA), representing the metal riser and fiber-reinforced composite marine riser, respectively, which differ greatly in modulus. Two types of boundary conditions were considered, which were simple supports at both ends (S-S) and simple and fixed supports at each end (S-F). The top tension forces were chosen as 10 N and 30 N, respectively. In terms of the flow velocities, 0.3 m/s and 0.7 m/s were used. For the wave types, the small wave had a period of 1.0 s and a wave height of 5 cm while the large wave had a period of 2.0 s and a wave height of 15 cm. The dynamic response of the riser under 32 different working conditions was studied experimentally, and through the analysis of the experimental data, the effects of various parameters on the dynamic response of the risers were obtained. The results show that the amplitude of the riser was negatively correlated with the elastic modulus, the number of constraints, and the magnitude of the top tension, while it was positively correlated with the flow velocity and wave size. Moreover, the sequences of importance were b3 (flow velocity) > b6 (modulus) > b1 (number of constraints) > b2 (top tension force) > b5 (wave height) > b4 (wave period) for the vibration of the riser in the in-flow direction and b3 (flow velocity) > b1 (number of constraints) > b6 (modulus) > b2 (top tension force) > b5 (wave height) > b4 (wave period) for the vibration of the riser in the cross-flow direction, respectively, according to the multiple linear regression calculation.

Nano-Fe promotes accumulation of phytoestrogens and volatile compounds in Trifolium pratense flowers - Yitong Li; Run Li; Xiaoyan Ren; Tian Wang; Haitao Yu; Quan Liu (Theoretical and Experimental Plant Physiology, 2023)

Projected change of East-Asian winter precipitation related to strong El Niño under the future emission scenarios - Yu Huang; Hong-Li Ren; Jong-Seong Kug; Run Wang; Jingxin Li (Climatic Change, 2023)

Simultaneous regulation of Li-ion intercalation and oxygen termination decoration on Ti3C2Tx MXene toward enhanced oxygen electrocatalysis for Li-O2 batteries - Shidong Song; Fangfang Yin; Yue Fu; Jiahao Ren; Junjie Ma; Yanan Liu; Run Ma; Wanyu Ye (Chemical Engineering Journal, 2023)

Numerical simulation of seasonal snow in Tianshan Mountains - Yan-run Ren; Yao-nan Zhang; Jian-sheng Hao; Yong-ping Shen; Guo-hui Zhao; Cong Li (Journal of Mountain Science, 2021)

Leading modes of Asian–Australian monsoon interannual variability as represented in CMIP5 models - Fang Zhou; Hong‐Li Ren; Ming‐Hong Liu; Run Wang; Kai Huang (International Journal of Climatology, 2021)
The Asian–Australian monsoon (AAM) exerts a strong impact on the regional climate. The ability of climate models to simulate the AAM is of great importance. This study evaluates the performance of 26 models, which participate in the Coupled Model Intercomparison Project phase 5 (CMIP5), in representing features of the leading modes of the AAM interannual variability. This is achieved by diagnosing quantitative metrics derived from a Season‐reliant Empirical Orthogonal Function (S‐EOF) analysis, and plausible external forcing contributing to the simulation results are presented. Our results show that the CMIP5 models can generally capture the spatial patterns of the leading modes of AAM interannual variability during El Niño development periods because of strong air–sea interactions. The variance percentage explained by the first two S‐EOF modes is found to be closely related to the amplitude of the El Niño‐Southern Oscillation (ENSO) in the models. In contrast, simulation of the periodicity remains challenging, and the models show deficiencies in the accurate capture of periodic characteristics. Models with realistic ENSO simulations typically perform well in simulating S‐EOF1, and the key to improving the simulation of S‐EOF2 is the greater intensity of the simulated field of background heating over the Northwest Pacific warm pool. The multimodel ensemble (MME) performs better than most of the 26 individual models. Models in the MME with better ENSO simulation and stronger warm pool heating are found to be better able to represent the relationships between the first two leading S‐EOF modes and ENSO, although biases remained.

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

A Review of Research on Tropical Air-Sea Interaction, ENSO Dynamics, and ENSO Prediction in China - Hong-Li Ren; Fei Zheng; Jing-Jia Luo; Run Wang; Minghong Liu; Wenjun Zhang; Tianjun Zhou; Guangqing Zhou (Journal of Meteorological Research, 2020)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Hydrogen Peroxide and Strigolactones Signaling Are Involved in Alleviation of Salt Stress Induced by Arbuscular Mycorrhizal Fungus in Sesbania cannabina Seedlings - Cun-Cui Kong; Cheng-Gang Ren; Run-Zhi Li; Zhi-Hong Xie; Ji-Ping Wang (Journal of Plant Growth Regulation, 2017)

Upper-ocean dynamical features and prediction of the super El Niño in 2015/16: A comparison with the cases in 1982/83 and 1997/98 - Hong-Li Ren; Run Wang; Panmao Zhai; Yihui Ding; Bo Lu (Journal of Meteorological Research, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

An Observational Study of Autologous Bone Marrow-Derived Stem Cells Transplantation in Seven Patients with Nervous System Diseases: A 2-Year Follow-Up - Chao Ren; Run-lu Geng; Wei Ge; Xiao-Yun Liu; Hao Chen; Mei-Rong Wan; De-Qin Geng (Cell Biochemistry and Biophysics, 2014)

Selective pressure dominates the synonymous codon usage in parvoviridae - Sheng-Lin Shi; Yi-Ren Jiang; Yan-Qun Liu; Run-Xi Xia; Li Qin (Virus Genes, 2013)